2012
DOI: 10.1159/000341815
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Gene Polymorphisms in Sudden Sensorineural Hearing Loss

Abstract: Background: Heat shock proteins protect cells and tissues against different types of damage. Previous studies have revealed that the serum level of heat shock protein 70 (HSP70) increases in sudden sensorineural hearing loss (SSNHL) patients. We hypothesized that genetic variants of the HSP70 gene are associated with susceptibility to SSNHL. Methods: We conducted a case-control study with 160 SSNHL cases and 178 controls. Three tagging single nucleotide polymorphisms (SNPs) were selected. The genotypes were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…According to the literature [Chien et al, 2012;Um et al, 2013], other genes might also have an impact on the presence of SSNHL, emphasizing that more studies are necessary to learn about the precise pathogenesis of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature [Chien et al, 2012;Um et al, 2013], other genes might also have an impact on the presence of SSNHL, emphasizing that more studies are necessary to learn about the precise pathogenesis of SSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of SSNHL are not known, various causes including viral infection, vascular disease and autoimmunity have been anticipated as the primary cause of the disease [Chien et al, 2012;Um et al, 2013]. However, it has so far been difficult to attribute one particular mechanism to individual cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross et al [Gross et al, 2008] found that the serum anti-HSP70 antibody and antiphospholipid antibody were significantly higher than the normal level in patients with SSNHL and the prognosis of SSNHL patients with positive anti-HSP70 antibody was better than that of negative patients, which indicated that HSP70 gene mutation may be associated with SSNHL. Subsequently, Chien et al [2012] described a significant association between one SNPs of HSP70 genes (rs2075800) and SSNHL. After haplotype analysis for three SNPs of HSP70 genes (rs2075800*, rs1043618, rs2763979), the haplotype TGC was found obviously different between healthy people and SSNHL patients.…”
Section: Hsp70 Genementioning
confidence: 99%
“…In the past 20 years, a series of disease susceptibility genes, such as MTHFR, ITGB3, PRKCH, and HSP70, have been identified in SSNHL [Ballesteros et al, 2012;Chien et al, 2012;Shu et al, 2015;Uchida et al, 2011], indicating that the genetic factor may play a significant role in patients with SSNHL. Since most of these studies have a relatively small sample size and commonly use particular ethnic groups as research objects, the result is hard to extrapolate to the general population.…”
Section: Introductionmentioning
confidence: 99%